Mechanical properties and pre-oxidation behavior of spark plasma sintered B4C ceramics using (Ti3SiC2+CeO2/La2O3) as sintering aid. Issue 14 (1st October 2020) - Song, Qi; Zhang, Zhao-Hui; Hu, Zheng-Yang; Wang, Hao; Zhang, Yi-Fan; Li, Xian-Yu; Liu, Luo-Jin; Li, Sheng-Lin; Cheng, Xing-Wang
Abstract: B4 C ceramic with the addition of 5 wt % (Ti3 SiC2 + CeO2 /La2 O3 ) as sintering aids was fabricated by spark plasma sintering at a relatively low temperature of 1650 °C for 5 min at 80 MPa. The phase composition, microstructures, and comprehensive mechanical properties of the ceramics were studied in detail. The existence of reinforced second phase particles, the refinement of the matrix grains, the formation of residual stress along the grain boundaries and the appearance of the mixed fracture mode had a synergetic strengthening effect on the mechanical properties. The flexural strength, fracture toughness and Vickers hardness of B4 C ceramics reached 565.2 ± 21.8/551.0 ± 25.2 MPa, 6.28 ± 0.01/6.41 ± 0.12 MPa·m 0.5, and 28.51 ± 0.86/27.23 ± 1.08 GPa, respectively. In addition, to reduce the crack sensitivity of the ceramic, the ceramics were pre-oxidized at 800 °C for different durations. The flexural strength was increased by approximately 13.4% after the ceramic was oxidized at 800 °C for 45 min due to the crack-healing effect induced by the oxide glass B2 O3 on the ceramic surface.